Knowledge and Awareness of Thirdhand Smoke among Smokers and Non-smokers - A Comparative cross-sectional study - M, INDUMATHY.; R, PRADEEP KUMAR.; ARUMUGAM, I. MEIGNANA (The journal of contemporary issues in business and government, 2020)
Third-hand smoke (THS) is the residual tobacco smoke contaminant that remains after a cigarette is extinguished. It can react with the indoor air pollutant nitrous acid to produce a carcinogen. THS exposure may occur long after second-hand smoke appears (SHS). A cross sectional questionnaire study was conducted in which a close-ended self- administered 20 item questionnaire was prepared. The data was collected from the smokers and non-smokers. Demographic characteristics, tobacco use status, attitudes toward awareness of third hand smoke and its adverse effects, was filled by the surveyed subjects. A total of 100 members with the mean age of 15-45 years participated in the study. The awareness of Third hand smoke is more among the non-smokers than compared with the smokers. The precautionary principle, which is a “strategy to cope with possible risks where scientific understanding is yet incomplete,” is widely used in Europe and in radiation protection in the United States. Extended producer responsibility promotes total-lifecycle environmental improvements, placing economic, physical, and informational responsibilities onto the tobacco industry. Efforts to further reduce THS exposure may ultimately reduce tobacco- related diseases and preserve the health of non-smoking adults and children.